2012
DOI: 10.1002/app.36323
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of cellulose nanofibers from ionic liquids: The effect of different cosolvents

Abstract: Cellulose was electrospun with various concentrations of ionic liquid and cosolvent. Three different cosolvents were used in this study; dimethylacetamide (DMAc), dimethyl formamide (DMF), and dimethyl sulfoxide (DMSO). The cosolvents were added to modify the viscosity, electrical conductivity, and surface tension of the solutions. The solubility of cellulose in ionic liquids is highly affected by changes in solvent properties on the molecular level in the binary solvent systems. The difference in molecular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…Although, cellulose/IL/DMSO solutions behave as Newtonian fluids at very low cellulose concentration (<0.80 wt %), the solution viscosity increases with cellulose concentration and exhibits a shear-thinning behavior at higher shear rates [118]. Additionally, shear thinning behavior can be detected, as well with dimethylacetamide (DMAc) and dimethylformamide (DMF), at high fractions of IL [119]. As an alternative to water or organic solvents, viscosity reduction can be provided by carbon dioxide (CO 2 ) [120].…”
Section: Viscosity Of Concentrated Cellulose Solutions In Ilsmentioning
confidence: 99%
“…Although, cellulose/IL/DMSO solutions behave as Newtonian fluids at very low cellulose concentration (<0.80 wt %), the solution viscosity increases with cellulose concentration and exhibits a shear-thinning behavior at higher shear rates [118]. Additionally, shear thinning behavior can be detected, as well with dimethylacetamide (DMAc) and dimethylformamide (DMF), at high fractions of IL [119]. As an alternative to water or organic solvents, viscosity reduction can be provided by carbon dioxide (CO 2 ) [120].…”
Section: Viscosity Of Concentrated Cellulose Solutions In Ilsmentioning
confidence: 99%
“…Among the nanostructured celluloses, cellulose-based nanofibers are very interesting, due to relatively easy fabrication via the electrospinning process. Several solvents that directly dissolve cellulose have been used for electrospinning, including N-methyl-morpholine N-oxide/water (NMMO/ water), dimethylacetamide/lithium chloride (DMAc/LiCl), and ionic liquids [5][6][7][8]. However, these solvents have low volatility, and thus cannot completely evaporate during the electrospinning process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that appropriate cosolvents can be found by measuring solvatochromic parameters [20], which has been reported for e.g., N-methylimidazole (MIM) [21]. Dimethylsulfoxide (DMSO), N,N-dimethylacetamide (DMAc), and dimethylformamide (DMF) have been used together with BMIMCl and other ILs to increase reactivity and/or processability of cellulose in solution [22,23]. Cosolvents can be used to facilitate derivatization, e.g., molecular bases such as pyridine used as catalysts in tosylation reactions [21] and for viscosity modification [24].…”
Section: Introductionmentioning
confidence: 99%